Preparation method and application of copper-silver bimetal organic framework compound / rhodium electrode for electrochemically detecting total nitrogen
By preparing copper-silver bimetallic organic frame compound/rhodium electrode (CuAg-MOF/Rh composite electrode), the problem of long oxidation process, the need for toxic reagents and insufficient electrode stability in the existing electrochemical detection methods is solved, and high sensitivity and rapid detection of total nitrogen in water is achieved.
Patent Information
- Application Number
- CN202411727643.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
AI Technical Summary
When existing electrochemical detection methods detect total nitrogen in water quality, the oxidation process takes a long time and require toxic chemical reagents. The stability and response sensitivity of a single copper electrode are insufficient and are susceptible to interference from environmental factors.
CuAg-MOF was prepared by hydrothermal reaction using copper-silver bimetallic organic frame compound/rhodium electrode (CuAg-MOF/Rh composite electrode), and a nanometallic Rh layer was formed on its surface, and the stability and reactivity of the electrode were improved by magnetron sputtering and ion etching treatment.
The rate and sensitivity of electrocatalytic reduction of nitrate is improved, the stability of the electrode is enhanced, and the total nitrogen in the water can be detected quickly and accurately under mild conditions without secondary pollution.
Smart Images

Figure CN119534579A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electrochemical technology, and in particular to a preparation method and application of a copper-silver bimetallic organic framework compound / rhodium electrode for electrochemical detection of total nitrogen. Background Art
[0002] Total nitrogen is a key indicator for measuring water quality, including the total amount of inorganic and organic nitrogen in various forms in water. Excessive nitrogen content in water can lead to massive reproduction of microorganisms, consume dissolved oxygen in the water, and deteriorate water quality. Excessive nitrogen content in water can lead to eutrophication of water bodies, promote massive reproduction of water microorganisms, and deteriorate water quality.
[0003] The detection methods of total nitrogen in water quality mainly include national standard methods and some emerging technologies. The national standard methods mainly include alkaline potassium persulfate digestion-ultraviolet spectrophotometry and naphthylethylenediamine hydrochloride spectrophotometry. These two methods calculate the total nitrogen content by oxidizing organic nitrogen and inorganic nitrogen compounds in water samples into nitrates and then measuring the nitrate concentration. Although these methods are highly accurate, the oxidation process usually takes up to 30 minutes and requires a variety of toxic and harmful chemical reagents, which are prone to secondary pollution.
[0004] Chromatography is a laboratory-level technique that can efficiently separate and detect nitrates and nitrites in water samples, but the sample pretreatment steps are complicated and the equipment cost is high. Compared with existing methods, the electrochemical method has the advantages of simple operation, rapid reaction, simple equipment, no secondary pollution, and mild reaction conditions. After the nitrogen-containing substances in the water sample are converted into nitrates, the electrode is used to reduce the nitrate to ammonia, and the current signal is measured to calculate the nitrate content. Recent studies have found that metallic copper and its oxides are electrocatalytic materials with good electrocatalytic reduction of nitrates. However, the electrocatalytic reduction ability of a single copper electrode is insufficient, and the surface area of the prepared metallic copper or copper oxide electrode is small, resulting in low response sensitivity in the electrochemical detection of nitrates, and the stability of the copper electrode is poor, which is easily interfered by pH and chloride ions in practical applications. Summary of the invention
[0005] In order to solve the above technical problems, an embodiment of the present invention provides a preparation method and application of a copper-silver bimetallic organic framework compound / rhodium electrode for electrochemical detection of total nitrogen.
[0006] To achieve the above object, the embodiments of the present invention adopt the following technical solutions:
[0007] In one aspect, the present invention provides a method for preparing a copper-silver bimetallic organic framework compound / rhodium electrode for electrochemical detection of total nitrogen, comprising the following steps:
[0008] A. preparing a mixed solution of terephthalic acid, silver nitrate and a solvent, and placing the foamed copper in the mixed solution for hydrothermal reaction to obtain a copper-silver bimetallic organic framework compound;
[0009] B. Forming a rhodium film layer outside the copper-silver bimetallic organic framework compound in step A, and finally annealing and removing impurities to obtain a copper-silver bimetallic organic framework compound / rhodium electrode material.
[0010] In some embodiments, in step A, the volume ratio of the mass of terephthalic acid and silver nitrate to the solvent is (0.15-0.6) g: (0.05-0.2) g: (15.7-48) mL.
[0011] In some embodiments, the solvent is a mixture of N,N-dimethylformamide, ethylene glycol and water, and the volume ratio of N,N-dimethylformamide, ethylene glycol and water is (15-45): (0.5-2): (0.2-1).
[0012] In some embodiments, in step A, the temperature of the hydrothermal reaction is 120-180° C., the reaction time is 3-9 hours, and the heating rate is 5-20° C. / min.
[0013] In some embodiments, in step B, the rhodium film layer is formed by the following method: a copper-silver bimetallic organic framework compound is placed in a magnetron sputtering coating machine, metal rhodium is used as a target material, and a rhodium film layer with a thickness of 50 to 400 nm is formed outside the copper-silver bimetallic organic framework compound by magnetron sputtering.
[0014] In some embodiments, the vacuum degree of the magnetron sputtering is 1×10 -5 ~5.5×10 -4 Pa, grating is 10-30°, bias is 90-110V, current is 10-20A, and sputtering time is 3-30min.
[0015] In some embodiments, in step B, the annealing temperature is 200-400° C., and the annealing atmosphere is argon or nitrogen.
[0016] In some embodiments, in step B, the impurity removal is performed by the following method: after annealing the rhodium film layer formed on the copper-silver bimetallic organic framework compound, the film is placed in a reactive ion etcher, argon is used as the working gas, nitrogen is used as the process gas, and the vacuum is reduced to 2×10 -5 ~1×10 -4 After Pa, the surface was treated at a power of 80-120 W for 5-10 min. During the whole process, the argon flow rate was maintained at 80-100 mL / min and the nitrogen flow rate was controlled at 5-15 mL / min.
[0017] On the other hand, the present invention also provides a copper-silver bimetallic organic framework compound / rhodium electrode prepared by the above-mentioned preparation method.
[0018] On the other hand, the present invention also provides an application of the copper-silver bimetallic organic framework compound / rhodium electrode in total nitrogen detection.
[0019] When applied to total nitrogen detection, the following method is adopted: the total nitrogen electrochemical detection method of the present invention is to use the current pre-treatment equipment to oxidize all nitrogen elements in the water into nitrate nitrogen; the copper-silver bimetallic organic framework compound / rhodium electrode material (recorded as CuAg-MOF / Rh composite electrode) is used as the working electrode, the saturated calomel electrode is used as the reference electrode, and the platinum wire is used as the auxiliary electrode to form a three-electrode system, and the electrochemical workstation is used to perform cyclic voltammetry scanning to complete the total nitrogen detection; wherein in the cyclic voltammetry curve, when the working electrode voltage is scanned to -1.1V (vs.SCE) in the negative direction, CuAg-MOF / Rh rapidly electrocatalytically reduces nitrate ions to nitrite ions or ammonium ions. By measuring the reduction current at this potential, a linear relationship between the reduction current and the nitrate nitrogen concentration can be established, thereby calculating the total nitrogen value.
[0020] Compared with the prior art, the present invention has at least the following beneficial effects:
[0021] In the CuAg-MOF / Rh composite electrode provided by the present invention, the porous Cu, Ag bimetallic framework compound (denoted as CuAg-MOF) has a high specific surface area, provides abundant Cu, Ag active sites, and the two metal sites produce a synergistic effect to accelerate the electrocatalytic reduction of nitrate. A layer of nano-metal Rh layer is sputtered on the surface of CuAg-MOF by magnetron sputtering. On the one hand, Rh covers CuAg-MOF to improve its stability, and on the other hand, the electrocatalytic hydrogen adsorption and desorption ability of nano-metal Rh can accelerate the electrocatalytic reduction rate of nitrate CuAg-MOF. Finally, annealing and ion etching treatment can clean the electrode surface, expose and generate more active sites, and improve the composite electrode to have a very high electrocatalytic reduction ability for nitrate. When the present electrode is applied to the detection of total nitrogen, the electrode has a stronger voltammetric response to nitric acid, and has good stability, and can achieve the advantages of high sensitivity and rapid detection of total nitrogen in water. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The scanning electron microscope photographs of the copper foam, CuAg-MOF composite electrode and CuAg-MOF / Rh composite electrode in Example 1;
[0023] Figure 2 is the standard curve of the two electrodes CuAg-MOF and CuAg-MOF / Rh in Example 1;
[0024] Figure 3 The standard curve of the response of the CuAg-MOF / Rh composite electrode in Example 1 to total nitrogen in the presence of chloride ions (the concentration is 3 times the corresponding total nitrogen concentration);
[0025] Figure 4 This is the response current value of the CuAg-MOF / Rh composite electrode in Example 1 to 1 mg / L total nitrogen within 30 days. DETAILED DESCRIPTION
[0026] The following will be combined with the accompanying drawings to clearly and completely describe the technical solutions in some embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, rather than all the embodiments. Based on the embodiments provided by the present disclosure, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present disclosure.
[0027] Example 1
[0028] The commercial copper foam raw material (copper content 99.99wt%) was processed into a copper foam sheet with a size of 20mm×10mm×2mm by cutting process, and ultrasonic cleaning was performed by ethanol. The copper foam sheet was placed in an autoclave, and 0.2g terephthalic acid, 0.1g silver nitrate (PTA), 25mL N,N-dimethylformamide (DMF), 1mL ethylene glycol, and 0.5mL water were added. The autoclave was heated at a rate of 10℃ / min, heated to 120℃ and kept warm for 6 hours to obtain a CuAg-MOF composite electrode. After washing and drying, the CuAg-MOF composite electrode was placed in a magnetron sputtering coating machine, and a layer of Rh film with a thickness of 300nm was sputtered on the CuAg-MOF composite electrode by magnetron sputtering using metal rhodium as the target material. The vacuum degree was 4×10 -5 Pa, grating 10°, bias 90V, current 20A, sputtering time 20min, high temperature 300℃ annealing to obtain CuAg-MOF / Rh composite electrode. Finally, the CuAg-MOF / Rh composite electrode was placed in an ion etcher with argon as working gas and nitrogen as process gas until the vacuum dropped to 8×10 -5 Pa, the electrode surface was treated at a power of 85 W for 5 minutes. During the whole process, the argon flow rate was maintained at 90 ml / min and the nitrogen flow rate was controlled at 10 ml / min to obtain a CuAg-MOF / Rh composite electrode (i.e., a copper-silver bimetallic organic framework compound / rhodium electrode).
[0029] The microstructure of the special CuAg-MOF / Rh composite electrode prepared in this example was observed using a scanning electron microscope (SEM). Figure 1 As shown, from Figure 1It can be seen that compared with the CuAg-MOF composite electrode, the CuAg-MOF composite electrode with a lamellar structure is coated with Rh, and the CuAg-MOF / Rh composite electrode in this embodiment forms a coated microstructure, which helps to increase the specific surface area of the electrode, increase the adsorption capacity and reaction area of the electrode, and is beneficial to the adsorption and catalytic reduction of nitrate on the electrode surface.
[0030] Example 2
[0031] The commercial copper foam raw material (copper content 99.99wt%) was processed into a copper foam sheet with a size of 20mm×10mm×2mm by cutting process, and ultrasonic cleaning was performed by ethanol. The copper foam sheet was placed in an autoclave, and 0.15g terephthalic acid, 0.05g silver nitrate (PTA), 15mL N,N-dimethylformamide (DMF), 0.5mL ethylene glycol, and 0.2mL water were added. The autoclave was heated to 120℃ at a heating rate of 5℃ / min and kept warm for 3 hours to obtain a CuAg-MOF composite electrode. After washing and drying, the CuAg-MOF composite electrode was placed in a magnetron sputtering coating machine, and a layer of nano-Rh film with a thickness of 250nm was sputtered on the CuAg-MOF composite electrode by magnetron sputtering using metal rhodium as the target material. The vacuum degree was 3×10 -5 Pa, grating 10°, bias 95V, current 15A, sputtering time 20min, annealing at 200℃ to obtain the CuAg-MOF / Rh composite electrode. Finally, the CuAg-MOF / Rh composite electrode was placed in an ion etcher with argon as the working gas and nitrogen as the process gas until the vacuum degree dropped to 8×10 -5 Pa, the electrode surface was treated at a power of 80 W for 5 minutes. During the whole process, the argon flow rate was maintained at 80 ml / min and the nitrogen flow rate was controlled at 5 ml / min to obtain the CuAg-MOF / Rh composite electrode.
[0032] Example 3
[0033] The commercial copper foam raw material (copper content 99.99wt%) was processed into a copper foam sheet with a size of 20mm×10mm×2mm by cutting process, and ultrasonic cleaning was performed by ethanol. The copper foam sheet was placed in an autoclave, and 0.4g terephthalic acid, 0.15g silver nitrate (PTA), 30mL N,N-dimethylformamide (DMF), 1.5mL ethylene glycol, and 0.6mL water were added. The autoclave was heated at a rate of 15℃ / min, heated to 150℃ and kept warm for 6 hours to obtain a CuAg-MOF composite electrode. After washing and drying, the CuAg-MOF composite electrode was placed in a magnetron sputtering coating machine, and a layer of Rh film with a thickness of 300nm was sputtered on the CuAg-MOF composite electrode by magnetron sputtering using metal rhodium as the target material. The vacuum degree was 5×10 -5Pa, grating 10°, bias 100V, current 15A, sputtering time 25min, annealing at 300℃ to obtain the CuAg-MOF / Rh composite electrode. Finally, the CuAg-MOF / Rh composite electrode was placed in an ion etcher with argon as the working gas and nitrogen as the process gas until the vacuum degree dropped to 6×10 -5 Pa, the electrode surface was treated at a power of 110 W for 7 minutes. During the whole process, the argon flow rate was maintained at 90 ml / min and the nitrogen flow rate was controlled at 12 ml / min to obtain the CuAg-MOF / Rh composite electrode.
[0034] Example 4
[0035] The commercial copper foam raw material (copper content 99.99wt%) was processed into a copper foam sheet with a size of 20mm×10mm×2mm by cutting process, and ultrasonic cleaning was performed by ethanol. The copper foam sheet was placed in an autoclave, and 0.5g terephthalic acid, 0.2g silver nitrate (PTA), 40mL N,N-dimethylformamide (DMF), 1.5mL ethylene glycol, and 0.8mL water were added. The autoclave was heated at a rate of 15℃ / min, heated to 160℃ and kept warm for 8 hours to obtain a CuAg-MOF composite electrode. After washing and drying, the CuAg-MOF composite electrode was placed in a magnetron sputtering coating machine, and a layer of Rh film with a thickness of 320nm was sputtered on the CuAg-MOF composite electrode by magnetron sputtering using metal rhodium as the target material. The vacuum degree was 3×10 -5 Pa, grating 20°, bias 105V, current 18A, sputtering time 25min, annealing at 350℃ to obtain the CuAg-MOF / Rh composite electrode. Finally, the CuAg-MOF / Rh composite electrode was placed in an ion etcher with argon as the working gas and nitrogen as the process gas until the vacuum degree dropped to 3×10 -5 Pa, the electrode surface was treated at a power of 110 W for 5 minutes. During the whole process, the argon flow rate was maintained at 95 ml / min and the nitrogen flow rate was controlled at 10 ml / min to obtain the CuAg-MOF / Rh composite electrode.
[0036] Example 5
[0037] The commercial copper foam raw material (copper content 99.99wt%) was processed into a copper foam sheet with a size of 20mm×10mm×2mm by cutting process, and ultrasonic cleaning was performed by ethanol. The copper foam sheet was placed in an autoclave, and 0.6g terephthalic acid, 0.2g silver nitrate (PTA), 45mL N,N-dimethylformamide (DMF), 2mL ethylene glycol, and 1mL water were added. The autoclave was heated at a rate of 20℃ / min, heated to 180℃ and kept warm for 9 hours to obtain a CuAg-MOF composite electrode. After washing and drying, the CuAg-MOF composite electrode was placed in a magnetron sputtering coating machine, and a layer of Rh film with a thickness of 380nm was sputtered on the CuAg-MOF composite electrode by magnetron sputtering using metal rhodium as the target material. The vacuum degree was 4×10 -5 Pa, grating 30°, bias 110V, current 20A, sputtering time 30min, annealing at 300℃ to obtain the CuAg-MOF / Rh composite electrode. Finally, the CuAg-MOF / Rh composite electrode was placed in an ion etcher with argon as the working gas and nitrogen as the process gas until the vacuum degree dropped to 5×10 -5 Pa, the electrode surface was treated at a power of 120 W for 10 minutes. During the whole process, the argon flow rate was maintained at 90 ml / min and the nitrogen flow rate was controlled at 10 ml / min to obtain the CuAg-MOF / Rh composite electrode.
[0038] Example 6
[0039] The commercial copper foam raw material (copper content 99.99wt%) was processed into a copper foam sheet with a size of 20mm×10mm×2mm by cutting process, and ultrasonic cleaning was performed by ethanol. The copper foam sheet was placed in an autoclave, and 0.12g terephthalic acid, 0.15g silver nitrate (PTA), 30mL N,N-dimethylformamide (DMF), 1mL ethylene glycol, and 0.5mL water were added. The autoclave was heated at a rate of 15℃ / min, heated to 120℃ and kept warm for 6 hours to obtain a CuAg-MOF composite electrode. After washing and drying, the CuAg-MOF composite electrode was placed in a magnetron sputtering coating machine, and a layer of Rh film with a thickness of 180nm was sputtered on the CuAg-MOF composite electrode by magnetron sputtering using metal rhodium as the target material. The vacuum degree was 1×10 -5 Pa, grating 12°, bias 100V, current 15A, sputtering time 20min, annealing at 300℃ to obtain the CuAg-MOF / Rh composite electrode. Finally, the CuAg-MOF / Rh composite electrode was placed in an ion etcher with argon as the working gas and nitrogen as the process gas until the vacuum degree dropped to 7×10 -5Pa, the electrode surface was treated at a power of 85 W for 6 minutes. During the whole process, the argon flow rate was maintained at 90 ml / min and the nitrogen flow rate was controlled at 15 ml / min to obtain the CuAg-MOF / Rh composite electrode.
[0040] Test example: Application of copper foam loaded Cu / Ag / Rh composite electrode in total nitrogen detection
[0041] Water sample pretreatment:
[0042] The samples to be tested were treated with commercial digestion equipment (TDR-30S multifunctional intelligent digester produced by Shenzhen Tongao Technology Co., Ltd.) to oxidize the nitrogen in the water into nitrate nitrogen.
[0043] Electrochemical detection:
[0044] Test group: The CuAg-MOF / Rh composite electrode of Example 1 was used as the working electrode, the saturated calomel electrode was used as the reference electrode, and the platinum wire was used as the auxiliary electrode to form a three-electrode system. The electrodes were placed in 50 mL of total nitrogen standard samples with different concentrations. The distance between the working electrode and the auxiliary electrode was 1 cm. The CV test was started with the following test parameters: scanning voltage range: -1.15 to -0.1 V, scanning rate of 50 mV / s, and the current at -1.1 V of the CV curve was recorded at the same time. The current value at this voltage was used as a standard curve for the total nitrogen concentration. The total nitrogen value can be obtained by substituting the current value detected by the water sample into the standard curve.
[0045] Control group: The difference from the experimental group is that the CuAg-MOF composite electrode is used as the working electrode, and the other conditions remain unchanged.
[0046] pass Figure 2 From the standard curves of CuAg-MOF and CuAg-MOF / Rh electrodes, it can be seen that the response slope of the CuAg-MOF / Rh composite electrode to total nitrogen is much higher than that of the CuAg-MOF composite electrode, which has good sensitivity and is more conducive to the detection of total nitrogen.
[0047] pass Figure 3 The standard curve of the response of the CuAg-MOF / Rh composite electrode to total nitrogen in the presence of chloride ions (concentration is 3 times the corresponding total nitrogen concentration). It can be seen that the CuAg-MOF / Rh composite electrode has good anti-interference ability for chloride ions with a concentration 3 times higher under the same conditions.
[0048] pass Figure 4 The response current value of the CuAg-MOF / Rh composite electrode to 1 mg / L total nitrogen within 30 days. It can be seen that the average relative error of the current value within 30 days is 2.75%. The CuAg-MOF / Rh composite electrode has good stability in detecting total nitrogen.
[0049] In the description of this specification, specific features, structures, materials or characteristics may be combined in an appropriate manner in any one or more embodiments or examples.
[0050] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a copper-silver bimetallic organic framework compound / rhodium electrode for electrochemical detection of total nitrogen, characterized in that: The following steps are involved: A. preparing a mixed solution of terephthalic acid, silver nitrate and a solvent, and placing the foamed copper in the mixed solution for hydrothermal reaction to obtain a copper-silver bimetallic organic framework compound; B. Forming a rhodium film layer outside the copper-silver bimetallic organic framework compound in step A, and finally annealing and removing impurities to obtain a copper-silver bimetallic organic framework compound / rhodium electrode material.
2. The preparation method according to claim 1, characterized in that: In step A, the volume ratio of the mass of terephthalic acid and silver nitrate to the solvent is (0.15-0.6) g: (0.05-0.2) g: (15.7-48) mL.
3. The preparation method according to claim 1 or 2, characterized in that: The solvent is a mixture of N,N-dimethylformamide, ethylene glycol and water, and the volume ratio of N,N-dimethylformamide, ethylene glycol and water is (15-45): (0.5-2): (0.2-1).
4. The preparation method according to claim 1, characterized in that: In step A, the temperature of the hydrothermal reaction is 120-180° C., the reaction time is 3-9 hours, and the heating rate is 5-20° C. / min.
5. The preparation method according to claim 1, characterized in that: In step B, the rhodium film layer is formed by the following method: a copper-silver bimetallic organic framework compound is placed in a magnetron sputtering coating machine, metal rhodium is used as a target material, and a rhodium film layer with a thickness of 50 to 400 nm is formed outside the copper-silver bimetallic organic framework compound by magnetron sputtering.
6. The preparation method according to claim 5, characterized in that: The vacuum degree of the magnetron sputtering is 1×10 -5 ~5.5×10 -4 Pa, grating is 10-30°, bias is 90-110V, current is 10-20A, and sputtering time is 3-30min.
7. The preparation method according to claim 1, characterized in that: In step B, the annealing temperature is 200-400° C., and the annealing atmosphere is argon or nitrogen.
8. The preparation method according to claim 1, characterized in that: In step B, the impurity removal adopts the following method: after annealing the rhodium film layer formed on the copper-silver bimetallic organic framework compound, place it in a reactive ion etcher, use argon as the working gas and nitrogen as the process gas, and wait until the vacuum degree drops to 2×10 -5 ~1×10 -4 After Pa, the surface was treated at a power of 80-120 W for 5-10 min. During the whole process, the argon flow rate was maintained at 80-100 mL / min and the nitrogen flow rate was controlled at 5-15 mL / min.
9. A copper-silver bimetallic organic framework compound / rhodium electrode prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the copper-silver bimetallic organic framework compound / rhodium electrode according to claim 9 in total nitrogen detection.